2020
DOI: 10.1080/09500693.2020.1817607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of games on students’ emotions of learning science and achievement in chemistry

Abstract: This study investigated the time effect of cooperative games on students' emotions of learning science and the treatment effect on their chemistry achievement. This quasi-experimental study compared the use of cards, board games, and riddles, and the use of conventional paper-and-pencil exercises to learn the basics of chemical elements and compounds, for a duration of 4 weeks. One hundred and fourteen ninth graders at an urban public high school in Taipei were involved. The results revealed that the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 57 publications
(75 reference statements)
2
27
0
2
Order By: Relevance
“…There was no significant difference between genders. It further corroborates the findings of Chen, Husnaini and Chen [11] The results revealed that the experimental group had significantly higher positive emotion and lower negative emotion throughout the intervention period, high achievers decreased their positive emotion, and middle to high achievers increased their negative emotion. Furthermore, low and middle achievers performed better when using games.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…There was no significant difference between genders. It further corroborates the findings of Chen, Husnaini and Chen [11] The results revealed that the experimental group had significantly higher positive emotion and lower negative emotion throughout the intervention period, high achievers decreased their positive emotion, and middle to high achievers increased their negative emotion. Furthermore, low and middle achievers performed better when using games.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…CheN, Husnaini and Chen [11] investigated the time effect of cooperative games on students' emotions of learning science and the treatment effect on their chemistry achievement by compared the use of cards, board games, and riddles, and the use of conventional paper-andpencil exercises to learn the basics of chemical elements and compounds. Quasi-experimental design was adopted using 114 ninth graders at an urban public high school in Taipei.…”
Section: Fig 2 Cation Wheel Fig 2 Anion Wheelmentioning
confidence: 99%
“…Charsky and Ressler (2011) used a computer game to conduct a learning activity, which further validated this conclusion. Students' collaborative efforts resulted in a higher level of achievement for all (Chen et al, 2020). Students develop a supportive community by assisting one another, which improves each member's performance.…”
Section: Learning Motivationmentioning
confidence: 99%
“…Students learn from peers (team members provide tips or reasons for answers, curiosity, and questions). As asserted by Chen et al (2020), Cheng et al (2019), andvan Putten et al (2020), although the group or team seemed to rely on each other for support during the learning process, they also tried to complete the work on their own. Based on the observation notes, the students seemed to pay attention to each other's comments but the will to implement them was absent.…”
Section: Learning Motivationmentioning
confidence: 99%
“…Games can motivate students to learn actively and enjoyable [2]. Previous research has shown that the use of games in chemistry learning has a positive impact on student learning outcomes, engagement, and motivation [13][14][15][16]. Games can also build students' critical thinking.…”
Section: Introductionmentioning
confidence: 99%